2010
DOI: 10.1007/s10661-010-1807-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxicity in Rhamdia quelen (Pisces, Siluriformes) after sub-chronic contamination with Fipronil

Abstract: Diverse genetic biomarkers have been used to evaluate the effects of pollution by mutagenic agents such as metals and pesticides, as well as a large variety of chemical substances derived from human activities. This work researched the effects that an exposure of 60 days to the insecticide Fipronil (concentrations of 0.05, 0.10 and 0.23 μg/L) can cause in the fish Rhamdia quelen using Comet assay with gills, histopathological analysis of gills and the Piscine Micronucleus test and Nuclear Morphological Alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 43 publications
4
21
0
2
Order By: Relevance
“…France, Italy, Germany, and Slovenia, to ban its use [41]. The results presented in our study demonstrate the threat of fipronil to A. mellifera and verify that it causes motor and behavioral changes.…”
Section: Accepted Preprintsupporting
confidence: 74%
“…France, Italy, Germany, and Slovenia, to ban its use [41]. The results presented in our study demonstrate the threat of fipronil to A. mellifera and verify that it causes motor and behavioral changes.…”
Section: Accepted Preprintsupporting
confidence: 74%
“…Ghisi et al (2011) researched the effects of exposure of 60 days to the insecticide FP (concentrations of 0.05, 0.10, and 0.23 mg/L). They found that two concentrations-0.10 and 0.23 mg/L-of FP exposure caused the histopathological changes, nuclear morphological alterations, and DNA damage on the gills in R. quelen using the histopathologic analysis and the MN test/comet assay.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in rats explained that FP is quickly metabolized and residues are distributed in tissues, especially in fatty tissues under the skin and hair follicles (Hugnet et al, 1999). Ghisi et al (2011) evaluated the genotoxicity of FP in Rhamdia quelen after subchronic contamination at three different concentrations (0.05, 0.1, 0.23 mg/L) using the comet and micronucleus (MN) test. They found that both 0.1 and 0.23 mg/L concentrations caused the most damage on DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the systemic insecticides fipronil and imidacloprid was banned in France, Italy, Germany, Slovenia (Ghisi et al, 2011), and Uruguay (Pareja et al, 2011) due to the high toxicity of these pesticides to pollinators. In Brazil, the authorization of the use of imidacloprid is under review process, and the aerial application of neonicotinoids (imidacloprid, tiamethoxam, clotianidine) and fipronil are forbidden in flowering crops (Ministério da Agricultura, Pecuária e Abastecimento, 2013).The review of the use authorization of fipronil and imidacloprid in countries where these products are authorized, such as Brazil, is important to reduce the risk that these substances represent to honey bees, whose loss affects beekeeping and compromises the survival and maintenance of native pollinators.…”
Section: Discussionmentioning
confidence: 99%